Satellite investigations of ice dynamics and supraglacial lake development in Greenland - Briggs, Kate Hannah (The University of Edinburgh, 2012)
This thesis aims to improve the current understanding of the processes which control the flow variability of Greenland Ice Sheet (GrIS) outlet glaciers. The most recent Intergovernmental Governmental Panel on Climate Change (IPCC) report (Meehl et al., 2007) identifies that a critical limitation to forecasts of sea-level rise are uncertainties in modelling the ice dynamics of the GrIS. Using Synthetic Aperture Radar (SAR) feature tracking, seasonal velocities of land- and marine- terminating glaciers in a region in the northeast of Greenland are measured. Records of air temperature in conjunction with seasonal observations of supraglacial lake development, sea ice conditions and ice front positions, derived from SAR imagery, are used to investigate the controls on the observed variations in ice velocity. A clear link between ice velocities and glacier hydrology is found. These findings are consistent with observations from other glaciers in Greenland and are suggestive of a universal hydrological forcing of ice velocity for the whole of the GrIS ablation zone. Lake drainage events have been identified as a key factor in linking atmospheric changes, glacier hydrology and ice velocities in Greenland. For modelling purposes, a means of parameterising the distribution and evolution of supraglacial lakes is therefore needed. Assuming that water will pond in surface depressions, this thesis assesses the ability of using Digital Elevation Models (DEMs) for this purpose. High resolution DEMs are created using Interferometric SAR (InSAR) for two, separate regions of the GrIS. The positions and areal extent of surface depressions are compared with those of lakes observed in optical satellite imagery. The level of correspondence between the two datasets is found to be poor as a result of the resolution of the DEMs and the physical differences between surface depressions and lakes (e.g. lakes may not fill the capacity of the depression). An alternative method for parameterising the seasonal distribution of supra-glacial lakes, by extrapolating trends observed in current lake distributions, is investigated. The locations and evolution of lakes in the west of Greenland during the summer of 2003 are mapped using 47 Moderate Resolution Imaging Spectroradiometer (MODIS) images. Clear trends are identified in the distributions of lakes with elevation and are linked to the seasonal melt-cycle and to changes in ice thickness and its influence on surface depressions, tensile stresses and hydrofracturing. It may be possible to extrapolate these trends to other regions and higher elevations on the ice sheet, thereby enabling the distribution of lakes to be parameterised in ice sheet models. The findings of this thesis help to contribute to the understanding of the interaction between climate and ice dynamics in the context of the GrIS.
Keywords: supraglacial lakes